2018
DOI: 10.7717/peerj.5451
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and individual determinants of oral health-related quality of life among five-year-old children: a multilevel analysis

Abstract: BackgroundContextual factors may influence oral health-related quality of life (OHRQoL) in children. The aim of the present study was to evaluate the influence of individual and contextual determinants of OHRQoL based on the perceptions of children.MethodsA cross-sectional study was conducted with a representative sample of 769 five-year-old children from public and private preschools in a city in the countryside of northeast Brazil. Parents/caregivers answered questionnaires addressing psychological aspects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The 2016 Global Burden of Disease Study reported that oral diseases globally affect at least 3.58 billion people, with 486 million children experience dental caries in their primary teeth worldwide [2]. The rates of ECC are the highest among the socially disadvantaged groups, such as those from a lower socio-economic status (SES), refugees, and ethnic minorities [3,4]. If left untreated, ECC may results in severe pain, abscesses, and may adversely impact children's general health, growth, and quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The 2016 Global Burden of Disease Study reported that oral diseases globally affect at least 3.58 billion people, with 486 million children experience dental caries in their primary teeth worldwide [2]. The rates of ECC are the highest among the socially disadvantaged groups, such as those from a lower socio-economic status (SES), refugees, and ethnic minorities [3,4]. If left untreated, ECC may results in severe pain, abscesses, and may adversely impact children's general health, growth, and quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who have used urgent dental services more than once have a greater probability of continuing to use such services as their main source of dental care 17 . Children and adolescents who seek healthcare services due to a toothache and for whom care is discontinued are subject to further episodes of pain and suffering, with impacts on daily activities, such as going to school, eating, playing and sleeping 10,11 . Besides treating and controlling the progression of dental caries, regular oral health follow-up by primary care services could avoid the recurrent demand for dental care due to episodes of pain in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of pain/discomfort of a dental origin is an important oral health outcome 8 . The literature has demonstrated that quality of life 9,10 and the perception of oral health in children and adolescents are strongly impacted by episodes of toothache 8,11 , which also exert an impact on parents/guardians in the form of emotional distress and missed days of work 12 . Despite advances in recent years in the field of collective oral health in Brazil 13 , toothache still affects a significant portion of children 14 and adolescents 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Schoolchildren and adolescents in schools with structural, organizational, curricular or processual characteristics that are more favourable to the oral health promotion have a lower prevalence of caries, [7][8][9][10][11][12] dental trauma, 7 dental pain 8 and a better oral health-related quality of life. [13][14][15] Oral health-related behaviours among schoolchildren such as toothbrushing, 2,12,16 consumption of foods with added sugar, 2,12,[16][17][18] tobacco consumption 2,[19][20][21][22] and alcohol intake 2,22 have also been investigated. The results vary, depending on the context, highlighting the need for further research involving these factors.…”
Section: Introductionmentioning
confidence: 99%